Improving Students’ Reading Comprehension Using PQ3R (Survey, Question, Read, Recite, and Review) at the Second Grade students of MTs. Al-Muini Sesela - Terasne; Hafiz, Hairori Sahrul (Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of the research was to know students’ reading comprehension PQ3R (Survey, Question, Read, Recite, and Review) at the second grade students of MTs. Al-Munini Sesela. It was classroom action research. It was done in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. Subject of the research was 28 students. Instruments used were students' test, students' and teacher’s activities used observation sheets, at the end of each cycle. The percentage of students' reading comprehension improves time by time. In pre-cycle, the percentage was 46% (not enough), in cycle I was 46% (not enough) and in cycle II was 82% (very good). Meanwhile, percentage of students' Activity also improves. In pre-cycle, the percentage is 52% (enough), in cycle I is 69% (good) and in cycle II was 80% (very good). It concludes that PQ3R ((Survey, Question, Read, Recite, and Review) able to improve students’ reading comprehension at the second grade students of MTs. Al-Munini Sesela.